Revision of the systematics of the Polystomoidinae (Platyhelminthes, Monogenea, Polystomatidae) with redefinition of Polystomoides Ward, 1917 and Uteropolystomoides Tinsley, 2017 - Chaabane Amira; Du Preez Louis; Johnston Gerald R.; Verneau Olivier (Parasite, 2022)
Polystomatids are platyhelminth parasites that infect mainly amphibians and freshwater turtles. For more than seven decades, chelonian polystomes were classified into three genera according to the number of hamuli, i.e. absent for Neopolystoma, one pair for Polystomoidella and two pairs for Polystomoides. Following re-examination of morphological characters, seven new genera were erected the past six years, namely Apaloneotrema, Aussietrema, Fornixtrema, Manotrema, Pleurodirotrema, Uropolystomoides and Uteropolystomoides. However, the polyphyly of Neopolystoma and Polystomoides on the one hand, and the nested position of Uteropolystomoides within a clade encompassing all Neopolystoma and Polystomoides spp. on the other, still raised questions about the validity of these genera. We therefore re-examined several types, paratypes and voucher specimens, and investigated the molecular phylogeny of polystomes sampled from the oral cavity of North American turtles to re-evaluate their systematic status. We show that all Polystomoides Ward, 1917, sensu Du Preez et al., 2022, Neopolystoma Price, 1939, sensu Du Preez et al., 2022 and Uteropolystomoides Tinsley, 2017 species, display vaginae that are peripheral and extend well beyond the intestine. We thus reassign all species of the clade to Polystomoides and propose nine new combinations; however, although Uteropolystomoides is nested within this clade, based on its unique morphological features, we propose to keep it as a valid taxon. Polystomoides as redefined herein groups all polystome species infecting either the oral cavity or the urinary bladder of cryptodires, with peripheral vaginae and with or without two pairs of small hamuli. Uteropolystomoides nelsoni (Du Preez & Van Rooyen 2015), originally described from Pseudemys nelsoni Carr is now regarded as Uteropolystomoides multifalx (Stunkard, 1924) n. comb. infecting three distinct Pseudemys species of North America.